KOREKSI BENTUK BERKAS CAHAYA LASER DIODA MENGGUNAKAN LENSA SILINDER - Ahmad Fauzi; Minarni ' (Komunikasi Fisika Indonesia, 2014)
Diode laser is kind of laser which uses semiconductor material as the gain medium. Diode laser is preferred insome applications because it is less expensive, compact, available in wide range of wavelength and power.Unfortunately, diode laser also has some disadvantages compared to other types of laser. The material shape oflaser diode produces unsymmetrical beam shape whereas most laser applications need a circular beam.Correction of the beam shape can be done using some optics such as anamorphics prism pairs, cylindrical lenspairs and optical fibers. In this study, the beam shape of two diode lasers are corrected by a pair of cylindricallens and measured using a photodiode and CCD camera. The first diode laser is a coherent 830 nm diode whichhas beam size in x and y axis respectively 0.65 mm, 1.35 mm. The second diode laser is aixiz 638 nm diodelaser which has beam size in x and y axis respectively 1.34 mm, 3.67 mm. The first diode laser was bestcorrected using a pair of cylindrical with a focal length of 75 mm and -12.7 mm, the distance between the lens is7.15 cm which produced beam size in x and y axis respectively 1.38 mm and 1.51 mm. The second diode laserwas best corrected using a pair of cylindrical lens with focal length 95 mm and -19 mm, the distance betweenthe lens is 8.1 cm which produced beam size in x and y axis respectively 1.95 mm and 2.2 mm.